Analisis Sejarah Ekonomi Terhadap Aliran Institusional - Anisa Sanas Nalamjra; Sasmi Ebigael Sinaga; Nur Aini Simbolon; Bonaraja Purba (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Institutional Economics is a school of thought in economics which contains the view that economic behavior, where a person or party is greatly influenced by certain institutions. In this case, institutions themselves have a fairly broad meaning and can be briefly defined as the